Efek NAA dan BAP terhadap Pembentukan Tunas, Daun, dan Tinggi Tunas Stek Mikro Nepenthes ampullaria Jack. - Heti Sartika Sari; Murni Dwiati; Iman Budisantosa (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
This study aimed to know the interaction between NAA and BAP as well as to obtain the best combination of both treatments in promoting the growth of Nepenthes ampullariamicrocutting.An experiment arranged in a factorial Randomized Complete Block Design (RCBD) wasapplied. Stem segments were used as blocks, where block I was the first segment followed by the next two segments as block II and III respectively. Two factors, i.e. NAA concentrations (0, 5, 10, 15 µM) and BAP concentrations (0, 9, 18, 27 µM) were employed giving rise to 16 combination of treatments. Each treatment combination was replicated threetimes resulting in 48 experimental units. The parametersmeasured were date of shoot initiation, date of root initiation, shoot number, leaf number, root number, length of longest leafand shoot height. The results showed that interactionbetween NAA and BAP in promoting N. ampullariamicrocutting growth was observed.  Combination between NAA of 0 µM and BAP of 18 µMwas found to be the best in promoting N. ampullariamicrocutting growth.Meanwhile, combination between NAA 0 µM and BAP 27 µM was recommended to promote shoot number of N. ampullaria.